Pharmacovigilance study on the increased use of antibiotics in pediatric treatment: Pharmacovigilance of antibiotic usage - Sakhare, Ghansham R; Yelwande, Purva; Suryawanshi, Sandhya; Ambhore, Kiran; Pawar, Rutuja; Jain, Kishor (Indian Journal of Pharmacy & Drug Studies, 2023)
Objective: To conduct the pharmacovigilance study on the increased use of antibiotics in pediatric treatment. Materials and Methods: A suitable, simple questionnaire associated with the study of pharmacovigilance assessment, for mainly the adverse drug reactions associated with the increased antibiotic use in pediatric treatment was designed and distributed among 200 families having children in the age groups of <1 to 8 year. This survey was done in Pune region. Amoxicillin, Tetracycline, Cephalexin, Doxycycline were the antibiotics selected for the study. Results: About self-medication more than 50% groups said they did self-medication. and major source for it was medicines leftover from previous prescriptions. Maximum response was obtained from 5–8year age group. ADR were detected with the usage of antibiotics in 66 percent of groups. When it comes to the intensity of an adverse drug reaction, 74% of respondents said it was light, 22% said it was moderate, and 4% said it was severe. Around 97 % groups said they went to doctor after occurrence of adverse drug reaction, 98 % percent groups said they were aware of the risks of self-medication. Majority of groups knew about adverse drug reactions reporting system. When it comes to awareness of increased antibiotic use leading to antibiotic resistance, 98% of groups were found aware of the problem. Discussion: Survey showed that families having small children experienced adverse drug reactions as a result of using any of the antibiotics Amoxicillin, Tetracycline, Cephalexin, or Doxycycline. Conclusion: In conclusion, our study strongly recommends that there is a great need to create awareness among the middleclass families having children to improve the reporting of ADR’s.